Basic facts about the United Nations (United Nations Department of Public Information, 2011)
Published since 1947, this handbook sets forth the structure of the United Nations, how it works and its main activities and driving concerns. Along with explaining the role played by the U.N. principal organs and the family of U.N. organizations, it explores U.N. contributions to international peace and security, economic and social development, human rights, humanitarian action, international law and decolonization. It also documents U.N. membership, peacekeeping operations and special observances, along with contact information for U.N. information centers.